Semiotic Analysis of BCA Advertisement Version “Don't Know, Give No!” on Youtube Media in Transaction Literacy - Setiawan, Ganda; Apriliani, Riski (Innovative: Journal Of Social Science Research, 2025)
This study aims to analyze the semiotics of BCA's “Don't Know, Kasih No!” advertisement on YouTube in terms of transaction literacy.The research method used is qualitative research with Roland Barthes' semiotic approach. This study uses data collection techniques obtained through documentation in the form of observations of scenes in the “Don't Know, Kasih No!” advertisement. The researcher analyzes the visuals, narrative, symbols, and other elements that appear in the advertisement. The data sources for this study are primary and secondary data. Data triangulation in this study is conducted by combining various sources and methods to obtain data validity and accuracy. The results of this study indicate that this advertisement not only functions as a promotional tool but also as an educational tool that raises important issues about digital transaction security. Through strong visual and symbolic representations, BCA encourages the public to be more critical, vigilant, and aware of potential traps in the digital world. Thus, this campaign can be understood as a form of financial literacy wrapped in a creative and meaningful narrative.